The Influence of a Suspended Cage Aquaculture Farm on the Hydrodynamic Environment in a Semienclosed Bay, SE China - Jiang, Xintao; Tu, Junbiao; Fan, Daidu (Frontiers in Marine Science, 2022)
Hydrodynamic responses of the aquaculture farm structures have been increasingly studied because of their importance in informing the aquaculture carrying capacity and ecological sustainability. The hydrodynamical effect of the suspended cage farm on flow structures and vertical mixing in the Sansha Bay, SE China, is examined using observational data of two comparative stations inside and outside the cage farm. The results show that current velocities are relatively uniform in the vertical except a bottom boundary layer outside the cage farm. Within the cage farm, the surface boundary layer produced by the cage-induced friction is obvious with current velocities decreasing upward, combining the classic bottom boundary layer to form a “double-drag layers” structure in the water column. The cage-induced drag decreases with water depth in the surface boundary layer with a maximum thickness of 3/4 the water column, and the current velocities can be reduced by 54%. The cage-induced friction can also significantly hinder the horizontal water exchange in the farm. Periodic stratification phenomena exist at both stations under the influence of lateral circulation. However, the subsurface (5–10 m below the sea surface) water column below the cage facilities is well-mixed as indicated by the vertical density profile, where the velocity shear (10–3 m–2) is about 10 times higher than that of the subsurface layer outside the cage farm. Therefore, we speculate that the well-mixing of the subsurface water column results from the local turbulence induced by the velocity shear, which in turn is produced by the friction of cage structures.